Uma Luz para atravessar a escuridão: A arte, um refletor para a educação em tempos de pandemia (Olhares, 2020)
This article reflects on the pandemic of COVID-19 and some of its consequences on education, such as the schools shutdown, the use of online teaching and the gradual return to face-to-face classes.  In this obscure scenario, art is thought as a tool that contributes to the sheltering and the sense of belonging of students in the scholar environment and a way to prevent further school dropout.
Keywords: art; education; school dropout; scholarship; pandemic; covid-19; coronavirus